Level of knowledge among obstetricians regarding diagnosis and treatment of maternal isoimmunization. Cross-sectional study in Bogotá (Colombia), 2012-2013 (2014)
Objective: To describe the level of knowledge regarding the diagnosis, treatment and prognosis of maternal isoimmunisation among Gynaecology and Obstetrics specialists, members of ABP (Asociación Bogotana de Perinatología). Materials and methods: Cross-sectional descriptive study. A questionnaire prepared by specialists in Maternal and Foetal Medicine (MFM) was administered between November 2012 and March 2013. Professionals practicing outside the national territory, those who had not practiced over the past ten years, and those who did not provide all the information required were excluded. The tool consisted of 18 questions organized in three domains: socio-demographic characteristics, information about clinical practice, and knowledge of the subject. A descriptive statistical analysis was used. Results: Of the 220 practitioners who were given the questionnaire, 127 (57.7%) completed the survey and were included in the analysis. The cutoff point for the indirect Coombs was correctly identified by 32% of the obstetricians and by 45% of the specialists in MFM. The role of middle cerebral artery velocimetry for the diagnosis of foetal anaemia was recognized by 43% and 62% of obstetricians and specialists in MFM, and 82% and 76%, respectively, would use it for the follow-up of foetuses with anaemia. Only 76% of obstetricians and 66% of MFM specialists recognized the indications for delivering the baby in cases of foetal anaemia, whereas 90% and 97%, respectively, identified the timing for cordocentesis and in utero transfusion. Finally, 37% of obstetricians and 48% of MFM specialists did not recognize the Queenan- Liley curve as an option in cases where there is no access to foetal Doppler. Conclusion: There is an important variability in the level of knowledge among obstetricians and MFM specialists regarding the diagnosis, treatment and follow-up of pregnant women with isoimmunisation. Additional studies are required to characterize the variability in clinical practice regarding the diagnosis and treatment of maternal isoimmunisation in Colombia.